Pharmacokinetics and tolerability of LIQ861, a novel dry-powder formulation of treprostinil. (November 2020) - Roscigno, Robert; Vaughn, Toby; Anderson, Stephanie; Wargin, William; Hunt, Thomas; Hill, Nicholas S.
A dry-powder inhaled formulation of treprostinil (LIQ861) produced using PRINT® technology offers a substantial advantage over current nebulized therapy. Treprostinil is a synthetic prostacyclin analogue that is currently approved for inhalation administration to patients with pulmonary arterial hypertension via nebulized Tyvaso® inhalation solution. LTI-101 was a phase 1, placebo-controlled, double-blind, randomized, single-center study that evaluated the ascending single-dose pharmacokinetics of LIQ861 in healthy subjects. Six sequential, escalating doses (25, 50, 75, 100, 125, and 150 mcg) were studied to investigate treprostinil exposure from LIQ861 inhalation. Subjects ( n = 57) were randomly assigned in a 3:1 ratio to receive a single dose of either LIQ861 ( n = 43) or placebo ( n = 14); 56 subjects completed all protocol-defined assessments. Following single-dose administration, treprostinil exposure from LIQ861 increased proportionally across the dose range studied, and the pharmacokinetics profile of treprostinil administered as LIQ861 was similar to prior reports of inhaled treprostinil. All doses of LIQ861 were generally well-tolerated with no deaths, serious adverse events, or dose-limiting toxicities. The most frequently reported treatment-emergent adverse events related to study drug administration were coughing and throat irritation, which are common to dry-powder formulations. Treatment-related treatment-emergent adverse events were reported more frequently at higher dose levels; however, all were assessed as mild in severity. We conclude that the pharmacokinetics profile of treprostinil using a dry-powder inhaled formulation increased in proportion to dose as anticipated and was similar to earlier reports of inhaled, nebulized treprostinil (Tyvaso®). Based on these results, a phase 3 study (INSPIRE; Clinicaltrials.gov Identifier NCT03399604) evaluating the long-term safety and tolerability of LIQ861 in patients with pulmonary arterial hypertension was initiated.